The Quality Characteristics of Dried Arils (Anardana) Prepared From Wild Pomegranate (Punica Granatum L.) Stored at Ambient Temperature Conditions (Bangladesh Journal of Botany, 2023)
Wild pomegranate fruit (Punica granatum L.) widely distributed in northern India is processed into a value added dried product namely anardana. During fruiting season fruits are available in bulk and traditional sun drying process is completely weather dependent which might lead to holding period before drying. Studies were carried out for the preparation of anardana at different intervals viz. 10, 20, 30 days from stored fruits at ambient temperature conditions (18-24oC). Physico-chemical, namely TSS, sugars and anthocyanins and sensory parameters of anardana increased significantly with the advancement of storage period. However, ascorbic acid and total phenols decreased with the storage period. After 20th day of storage of fruits, the various quality characteristics of anardana increased slightly, whereas, the acid content decreased slightly after 10th day of storage of fruits with faster decreasing rate after 20th day of storage. The best quality anardana in terms of quality characteristics can be prepared from the fruits stored up to 20 days period.Bangladesh J. Bot. 52(2): 411-418, 2023 (June)